Managing from Islamic perspectives: some preliminary findings from Malaysian Muslim managed organisations - Kazmi , Azhar; Ahmad , Khaliq (Center for Research on Islamic Management and Business and IISTE, 2013)
The idea for this work originally goes to back a few years to a critical comment made by an acquaintance with we were conversing on the developments in the area of management from Islamic perspectives. He asked, rather raised, a pointed question: do we have an example of an organization in reality that is run according to Islamic principles? we did not have an answer to that question then; I believe that we do not have a satisfactory answer to that question even now. This research work is an outcome of the frustration of not being able to find a satisfactory answer to that wellmeaning meaning question. Over the years, that frustration has been channeled into investigating and researching into whatever little material is available in the area of management from Islamic perspectives.